Percepç\~ao e qualidade: O acesso à internet banda larga e a avaliaç\~ao dos consumidores à luz da teoria da perspectiva - Paulo Sávio Leite Santos; Carlos Henrique Corseuil; Carla Peixoto Borges (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– This study aims to verify the effect of the download data transmission rate on the degree of satisfaction of consumers of fixed broadband internet access, evaluating whether this relationship is adequately explained by the three characteristics which, according to prospect theory (Kahneman e Tversky, 1979), guide people's decision-making. Aggregate secondary data from Satisfaction and Perceived Quality Surveys conducted annually and measurements collected in modems installed in consumers' homes are used, both produced by the National Telecommunications Agency in Brazil, between 2018 to 2020. From the perspective of first cognitive characteristic, the results suggest that consumers assess their satisfaction with service from a neutral reference point, associated in the study with the contracted download data transmission rate. The results also indicate adherence to the second cognitive characteristic, suggesting the reduce of consumers' sensitivity as increase or decrease the stimuli to which they are submitted. Additionally, direct tests did not show significant results indicating data adherence to the third cognitive characteristic. Nevertheless, relationships incidentally perceived during the second cognitive characteristic test suggest that consumer satisfaction is more strongly influenced by the delivery of TxD values below the contracted rate than by TxD values delivered above the contracted rate, suggesting consumers' aversion losses and, therefore, the adherence of data to the third cognitive characteristic.
10419/284866
Keywords: I31; D80; 330; internet; broadband; satisfaction; prospect theory